Gene expression in human NAFLD - Greco, Dario; Kotronen, Anna; Westerbacka, Jukka; Puig, Oscar; Arkkila, Perttu; Kiviluoto, Tuula; Laitinen, Saara; Kolak, Maria; Fisher, Rachel M.; Hamsten, Anders; Auvinen, Petri; Yki-Järvinen, Hannele (American journal of physiology: Gastrointestinal and liver physiology, 2008)
Despite the high prevalence of nonalcoholic fatty liver disease (NAFLD), little is known of its pathogenesis based on study of human liver samples. By the use of Affymetrix GeneChips (17,601 genes), we investigated gene expression in the human liver of subjects with extreme steatosis due to NAFLD without histological signs of inflammation (liver fat 66.0 ± 6.8%) and in subjects with low liver fat content (6.4 ± 2.7%). The data were analyzed by using sequence-based reannotation of Affymetrix probes and a robust model-based normalization method. We identified genes involved in hepatic glucose and lipid metabolism, insulin signaling, inflammation, coagulation, and cell adhesion to be significantly associated with liver fat content. In addition, genes involved in ceramide signaling (MAP2K4) and metabolism (UGCG) were found to be positively associated with liver fat content. Genes involved in lipid metabolism (PLIN, ACADM), fatty acid transport (FABP4, CD36), amino acid catabolism (BCAT1), and inflammation (CCL2) were validated by real-time PCR and were found to be upregulated in subjects with high liver fat content. The data show that multiple changes in gene expression characterize simple steatosis.